2011
DOI: 10.1128/mcb.01246-10
|View full text |Cite
|
Sign up to set email alerts
|

ck2-Dependent Phosphorylation of Progesterone Receptors (PR) on Ser81 Regulates PR-B Isoform-Specific Target Gene Expression in Breast Cancer Cells

Abstract: Progesterone receptors (PR) are critical mediators of mammary gland development and contribute to breast cancer progression. Progestin-induced rapid activation of cytoplasmic protein kinases leads to selective regulation of growth-promoting genes by phospho-PR species. Herein, we show that phosphorylation of PR Ser81 is ck2 dependent and progestin regulated in intact cells but also occurs in the absence of PR ligands when cells enter the G 1 /S phase of the cell cycle. T47D breast cancer cells stably expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(110 citation statements)
references
References 84 publications
3
106
1
Order By: Relevance
“…The stimulation of this enzyme and other kinases, could enhance the phosphorylation of PR and its co-activators in the presence of these antagonists (11)(12)(13). In fact, progestins bind to the PR, in cells' cytoplasm or membrane, thus inducing a cell signaling cascades that promotes phosphorylation of different proteins that could be involved in transcription 7,10,12 .…”
Section: Resultsmentioning
confidence: 99%
“…The stimulation of this enzyme and other kinases, could enhance the phosphorylation of PR and its co-activators in the presence of these antagonists (11)(12)(13). In fact, progestins bind to the PR, in cells' cytoplasm or membrane, thus inducing a cell signaling cascades that promotes phosphorylation of different proteins that could be involved in transcription 7,10,12 .…”
Section: Resultsmentioning
confidence: 99%
“…CK2 is a ubiquitously expressed kinase often up-regulated in many different types of cancer, including breast [55][56][57]. We and others have shown that CK2 phosphorylates PR on Ser81, a site that is basally phosphorylated; however, Ser81 phosphorylation levels increase markedly in response to ligand (or when cells enter S phase in the absence of ligand) [16,58]. PR phosphorylation at Ser81 is associated with a specific gene expression profile, which is correlated with pathways altered in breast cancer, including genes implicated in mammary stem cell maintenance and renewal [8,16].…”
Section: Post-translational Modifications and Molecular Interactions mentioning
confidence: 99%
“…Target gene selectivity is achieved not only through differential recruitment of PR [8,16], but also through associated transcriptional co-activators and repressors that are critical to PR function [9,10,46]. For example, pioneer factors are specialized subsets of transcription factors that open defined regions of chromatin, making it accessible for other transcription factors, like SRs (reviewed in [47,48]).…”
Section: Post-translational Modifications and Molecular Interactions mentioning
confidence: 99%
See 2 more Smart Citations